Morbidity and mortality pattern among babies admitted in special newborn care unit, Nellore, Andhra Pradesh, India - Chintha, Lakshmi Prasanna; Bollipo, Suneetha; Gottumukkala, Ravi Prabhu; Palepu, Sathya Prakash (International Journal of Contemporary Pediatrics, 2019)
Background: India contributes to 25% of neonatal mortality around the world. In developing countries neonatal mortality is quite high despite of advances in perinatal and neonatal care. The establishment of Special Newborn Care Units (SNCU) has been quite essential in reducing the neonatal morbidity and mortality. This study was conducted to assess the outcome of SNCU at a newly commissioned tertiary care teaching hospital at Nellore District, Andhra Pradesh. Aim of this study the morbidity and mortality patterns in an SNCU at tertiary care teaching hospital. Methods: It was a Retrospective, Hospital based, Descriptive study which was done among neonates admitted to SNCU, Nellore District, Andhra Pradesh for a period of 1 year (January 2015-December 2015). All the neonates admitted to SNCU, Nellore District, Andhra Pradesh during the study period were included in the study. Data was recorded in a predesigned semi-structured proforma. the data was entered into excel-sheet and analyzed using SPSS software version 21. Results: A total of 1015 babies were included in the study. Almost half 592(58.32%) were born in this hospital(inborn) and 423(41.67%) babies were referred from peripheral hospitals and nursing homes (out born). about 3/4th 767(75.5%) of babies were admitted in the first 24 hours of life. Almost half (53.4%) of the study group were male and 46.6% were female. The chief causes of admission in SNCU were Respiratory Distress Syndrome (40.2%) followed by birth asphyxia (19.1%), sepsis (13.3%), Neonatal Jaundice (9.9%) and prematurity (6.6%). In our study 63.0% patients were discharged, 19.3% had left hospital against medical advice, 10.1% died and 7.6% were referred to other institutions for specialized treatment. Conclusion: Respiratory Distress Syndrome, neonatal sepsis, neonatal hyperbilirubinemia, and HIE as the major causes of morbidity. Low Birth Weight and prematurity were the commonest contributors of death, therefore, attempts to prolong the pregnancy each week might improve the neonatal outcome considerably.